THE INFLUENCE OF PRODUCT QUALITY AND CONSUMER TRUST ON PURCHASING DECISIONS IN SHOPEE ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, SAM RATULANGI UNIVERSITY - Ambalau, Sweetly Yedia; Tielung, Maria V. J.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of product quality and consumer trust on purchasing decisions at Shopee among students of the Faculty of Economics and Business. The research method applied is a quantitative approach by distributing questionnaires to 100 respondents. Data were analyzed using multiple linear regression through SPSS. The results indicate that product quality has the most dominant influence on purchasing decisions, as reflected by the highest beta coefficient and strong significance level. This finding suggests that the better the product quality offered, the higher the likelihood that consumers will make a purchase. Consumer trust also shows a positive influence on purchasing decisions, although its effect is not as significant compared to product quality. Factors such as transaction security, platform reputation, and alignment with personal values contribute to shaping consumer trust in Shopee. These findings highlight that improving product quality and building consumer trust are crucial strategies for Shopee to maintain user loyalty and compete effectively in the increasingly competitive e-commerce market.   Keywords: Product Quality, Consumer Trust and Puechasing Decisions